Novel Standard Substance from Primary Hamster Kidney Cells for Quality Control of Human Rabies Vaccines in China - Leitai Shi; Jia Li; Xiaohong Wu; Shouchun Cao; Yunpeng Wang; Danhua Zhao; Yuhua Li (Vaccines)
Background: Host cell proteins (HCPs) from primary hamster kidney cells (PHKCs) used to produce rabies vaccines may cause an allergic reaction in humans, so these residual HCPs must be controlled. Establishing a national standard for PHKC HCP is very important to ensure the consistency of HCPs between batches of the vaccine and to standardize the control of HCPs. Objectives: We aimed to establish a novel national standard substance to determine the HCP residue in rabies vaccines produced with PHKCs. Methods: A two-step multi-laboratory collaborative collaboration was undertaken. In the first step, the protein concentration of the standard substance stock solution was determined using Lowry’s method. In the second step, the concentration of the candidate standard substance was determined with an enzyme-linked immunosorbent assay. Results: The concentration of the PHKC protein standard was 4.0 μg/mL (95% confidence interval: 3.5–4.4 μg/mL). Conclusions: The PHKC protein standard was approved by the Chinese National Committee on Standards for the quality control of PHKC-based rabies vaccines for human use, and it plays an important role in controlling the quality of these human vaccines.